2018
DOI: 10.1016/j.ymthe.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

miR-30 Family Reduction Maintains Self-Renewal and Promotes Tumorigenesis in NSCLC-Initiating Cells by Targeting Oncogene TM4SF1

Abstract: Increasing evidence indicates that tumor-initiating cells (TICs) are responsible for the occurrence, development, recurrence, and development of the drug resistance of cancer. MicroRNA (miRNA) plays a significant functional role by directly regulating targets of TIC-triggered non-small-cell lung cancer (NSCLC), but little is known about the function of the miR-30 family in TICs. In this study, we found the miR-30 family to be downregulated during the spheroid formation of NSCLC cells, and patients with lower m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…High TM4SF1 expression was associated with older patient age, smoking habits, and poor survival Ye et al, 2019 Lung cancer Kaplan-Meier analysis TM4SF1 expression was correlated with survival time, tumor size, lymph node metastasis, distant metastasis, overall survival, and clinical stage Fu et al, 2020 Lung cancer qRT-PCR Increased TM4SF1 expression was significantly associated with early post-operative relapse and shorter survival Kao et al, 2003 Lung cancer Kaplan-Meier survival analysis High TM4SF1 expression was correlated with shorter median overall survival and PFS Ma et al, 2018 Pancreatic cancer published profiles of the TCGA dataset TM4SF1 expression was associated with tobacco smoking, diabetes, tumor size, clinical stage, T stage, lymph node metastasis, distant tumor metastasis, tumor cell venous invasion, lymphatic invasion, and poor overall survival Xu D. et al, 2020 Pancreatic cancer IHC High TM4SF1 expression group showed better survival and lower locoregional recurrence rate than the low expression group Zheng B. et al, 2015 higher TM4SF1 expression levels have relatively good prognosis (Gordon et al, 2003(Gordon et al, , 2009(Gordon et al, , 2011. The function of TM4SF1 in different kinds of cancer was shown in Table 2.…”
Section: Clinical Prognosis Of Tm4sf1 Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…High TM4SF1 expression was associated with older patient age, smoking habits, and poor survival Ye et al, 2019 Lung cancer Kaplan-Meier analysis TM4SF1 expression was correlated with survival time, tumor size, lymph node metastasis, distant metastasis, overall survival, and clinical stage Fu et al, 2020 Lung cancer qRT-PCR Increased TM4SF1 expression was significantly associated with early post-operative relapse and shorter survival Kao et al, 2003 Lung cancer Kaplan-Meier survival analysis High TM4SF1 expression was correlated with shorter median overall survival and PFS Ma et al, 2018 Pancreatic cancer published profiles of the TCGA dataset TM4SF1 expression was associated with tobacco smoking, diabetes, tumor size, clinical stage, T stage, lymph node metastasis, distant tumor metastasis, tumor cell venous invasion, lymphatic invasion, and poor overall survival Xu D. et al, 2020 Pancreatic cancer IHC High TM4SF1 expression group showed better survival and lower locoregional recurrence rate than the low expression group Zheng B. et al, 2015 higher TM4SF1 expression levels have relatively good prognosis (Gordon et al, 2003(Gordon et al, , 2009(Gordon et al, , 2011. The function of TM4SF1 in different kinds of cancer was shown in Table 2.…”
Section: Clinical Prognosis Of Tm4sf1 Expressionmentioning
confidence: 99%
“… Bae et al (2011) reported that TM4SF1 was abundantly expressed on mesenchymal stem cells (MSCs) and functions as a surface protein marker that distinguishes MSCs from diverse cell sources, particularly fibroblastic connective tissues. MiR-30a/c significantly decreased the cancer stem-like characteristics of non-small cell lung cancer-initiating cells by inhibiting TM4SF1 in vitro and in vivo ( Ma et al, 2018 ). Silencing of TM4SF1 completely suppressed the transcription of the pluripotency factors sex-determining region Y box 2 (Sox2) and octamer-binding transcription factor-4 (Oct4), suggesting that TM4SF1 could promote the CSC traits of breast cancer ( Gao et al, 2016 ).…”
Section: Tm4sf1 Promotes Cancer Proliferation and Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the downregulation of miR-30, the overexpression of TM4SF1 in CSCs promotes tumorsphere formation and the proliferation of CSCs. In other words, miR-30 interferes with CSC development and induces cell apoptosis [40].…”
Section: Mir-30mentioning
confidence: 99%
“… 18 Competing endogenous RNAs (ceRNAs), natural decoys that compete for a common pool of microRNAs (miRNA, miR), represent a novel layer of gene regulation by systematically functionalizing miRNA response element (MRE)-harboring non-coding RNAs, such as long non-coding RNAs (lncRNAs), pseudogenes, and circular RNAs (circRNAs), and forming complex miRNA-mediated ceRNA networks. 19 , 20 , 21 , 22 , 23 The perturbation of ceRNA crosstalk will disrupt the balance of cellular processes and functions, leading to development of diseases such as cancer. 24 , 25 , 26 Recently, a study reported that lncRNAs H19 and HULC, stimulated by oxidative stress, regulate cell migration and invasion in CHOL by increasing the expression of IL-6 and CXCR4 in the inflammatory process using ceRNA methods of sponging let-7a/let-7b and miR-372/miR-373, respectively.…”
Section: Introductionmentioning
confidence: 99%